2022
DOI: 10.1021/acs.est.1c08342
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Clothing as a Vector for Transporting Airborne Particles and Pathogens across Indoor Microenvironments

Abstract: Evidence suggests that human exposure to airborne particles and associated contaminants, including respiratory pathogens, can persist beyond a single microenvironment. By accumulating such contaminants from air, clothing may function as a transport vector and source of "secondary exposure". To investigate this function, a novel microenvironmental exposure modeling framework (ABICAM) was developed. This framework was applied to a para-occupational exposure scenario involving the deposition of viable SARS-CoV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Similar limitations are seen in the application of agent-based models to simulate behavior of smaller groups of agents ( Brandon et al, 2020 ). There is work, for instance, to simulate exposure to household contaminants and airborne particles ( Kvasnicka et al, 2020 , Kvasnicka et al (2022) but the daily schedules used are simplified. A game-based simulation explored localized aspects of social, built, and natural environments related to congregate living ( Ottmann, 2020 ) but did not involve agent-based modeling.…”
Section: Human Behavior and Agent-based Modelingmentioning
confidence: 99%
“…Similar limitations are seen in the application of agent-based models to simulate behavior of smaller groups of agents ( Brandon et al, 2020 ). There is work, for instance, to simulate exposure to household contaminants and airborne particles ( Kvasnicka et al, 2020 , Kvasnicka et al (2022) but the daily schedules used are simplified. A game-based simulation explored localized aspects of social, built, and natural environments related to congregate living ( Ottmann, 2020 ) but did not involve agent-based modeling.…”
Section: Human Behavior and Agent-based Modelingmentioning
confidence: 99%
“…26−28 Recent studies have also reported airborne transmission of influenza in guinea pigs through the release of aerosolized fomites from contaminated body surfaces, 29,30 suggesting the role that nonrespiratory sources of particles from humans could play in the transmission of infectious diseases. Based on a microenvironmental exposure modeling framework, Kvasnicka et al 31 reported that SARS-CoV-2 transmission through resuspension from clothing is theoretically feasible, although the chances are 2 orders of magnitude lower than primary inhalation exposure to respiratory aerosols. Several studies have characterized and compared particle number concentrations (PNC) in both occupied and unoccupied indoor settings.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have been conducted to measure respiratory particle emissions during various human activities in clean environmental chambers, although without distinguishing between inert and infectious aerosols. In separate investigations, particle emissions from nonrespiratory sources such as clothing, , skin-shedding, resuspension from flooring, , and total particle emissions associated with human activities (i.e., a combination of both respiratory and nonrespiratory sources), have also been quantified. Recent studies have also reported airborne transmission of influenza in guinea pigs through the release of aerosolized fomites from contaminated body surfaces, , suggesting the role that nonrespiratory sources of particles from humans could play in the transmission of infectious diseases. Based on a microenvironmental exposure modeling framework, Kvasnicka et al reported that SARS-CoV-2 transmission through resuspension from clothing is theoretically feasible, although the chances are 2 orders of magnitude lower than primary inhalation exposure to respiratory aerosols. Several studies have characterized and compared particle number concentrations (PNC) in both occupied and unoccupied indoor settings. These studies have consistently reported higher PNC values in occupied indoor settings, suggesting an association between particle emissions and occupancy.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution poses an outstanding challenge to public health and even pathogen epidemics. Particulate matter (PM), a particulate component of air pollution, can increase the occurrence of various detrimental health effects. , Recently, mounting data have evidenced the implications of PMs in pathogen (e.g., bacteria and viruses) transmission and epidemic spreading. , For instance, many epidemiological studies have suggested that PM pollution is positively correlated to clinical influenza-like illness, active tuberculosis, and even the 2019 novel coronavirus (SARS-CoV-2). Of note, it has also been proposed that pathogens, such as bacteria, fungi, and viruses, could attach to dust particles or tiny droplets as bioaerosols. ,, Although a large amount of evidence indicates the possibility for pathogens traveling and transmitting through hitchhiking with PMs, much less is understood regarding the co-exposure of PMs and pathogens. In fact, numerous questions need to be answered, that is, how pathogens load on PMs, whether the co-exposure of PMs and pathogens together would induce more severe detrimental effects, and what are the long-term effects of co-exposure to PMs and pathogens together on the respiratory system.…”
Section: Introductionmentioning
confidence: 99%
“… 11 14 Of note, it has also been proposed that pathogens, such as bacteria, fungi, and viruses, could attach to dust particles or tiny droplets as bioaerosols. 8 , 12 , 15 17 Although a large amount of evidence indicates the possibility for pathogens traveling and transmitting through hitchhiking with PMs, much less is understood regarding the co-exposure of PMs and pathogens. In fact, numerous questions need to be answered, that is, how pathogens load on PMs, whether the co-exposure of PMs and pathogens together would induce more severe detrimental effects, and what are the long-term effects of co-exposure to PMs and pathogens together on the respiratory system.…”
Section: Introductionmentioning
confidence: 99%